The Volume‐Outcome Effect: Impact on Trial‐to‐Permanent Conversion Rates in Spinal Cord Stimulation. Issue 3 (3rd October 2016) - Murphy, Kelly Ryan; Han, Jing L.; Hussaini, Syed Mohammed Qasim; Yang, Siyun; Parente, Beth; Xie, Jichun; Lad, Shivanand P.
Abstract : Objectives: Conversion rates from trial leads to permanent spinal cord stimulation (SCS) systems have important implications for healthcare resource utilization (HCRU) and pain management. We hypothesized that there is a volume‐outcome effect, with chronic pain patients who visit high volume SCS implanters will have higher trial‐to‐permanent conversion rates. Materials and Methods: We designed a large, retrospective analysis using the Truven MarketScan database analyzing adult SCS patients with provider information available, with or without IPG implantation from the years 2007 to 2012 was designed. Patients were divided into three provider‐based groups: high (>25), medium (9–24), and low (3–8) volume providers. Univariate and multivariate models identified factors associated with successful conversion. Results: A total of 17, 850 unique trial implants were performed by 3028 providers. Of 13, 879 patients with baseline data available, 8981 (64.7%) progressed to permanent SCS. Higher volume providers were associated with slightly higher conversion rates (65.9% vs. 63.3% low volume, p  = 0.029), explant rates (9.2% vs. 7.7% medium volume, p  = 0.026), younger age (52.0 ± 13.4 years vs. 53.0 ± 13.4 years, p  = 0.0026), Medicare/Medicaid (47.8% vs. 35.0% low volume, p  < 0.0001), Southern region (53.5% vs. 38.9% low volume, p  < 0.0001), and higher Charlson comorbidity scores (1.0 [SD = 1.4], p  = 0.0002). Multivariate regression results showed female gender (1.13 [95% CI: 1.05–1.22], p  < 0.001) and high volume providers associated with higher odds of successful trial conversion (1.12 [95% CI: 1.02–1.22], p  = 0.014). Conclusions: In this nationwide analysis, high volume providers achieved higher trial‐to‐permanent SCS conversion rates than lower volume providers. The study has implications for both training requirements and referral patterns to delineate minimum implant experience necessary for provider proficiency. Future studies may be useful to understand HCRU differences.